Variable Selection in High Dimensional Linear Regressions with Parameter Instability - Alexander Chudik; M. Hashem Pesaran; Mahrad Sharifvaghefi (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper is concerned with the problem of variable selection when the marginal effects of signals on the target variable as well as the correlation of the covariates in the active set are allowed to vary over time, without committing to any particular model of parameter instabilities. It poses the issue of whether weighted or unweighted observations should be used at the variable selection stage in the presence of parameter instability, particularly when the number of potential covariates is large. Amongst the extant variable selection approaches, we focus on the One Covariate at a time Multiple Testing (OCMT) method. This procedure allows a natural distinction between the selection and forecasting stages. We establish three main theorems on selection, estimation post selection, and in-sample fit. These theorems provide justification for using unweighted observations at the selection stage of OCMT and down-weighting of observations only at the forecasting stage. The benefits of the proposed method as compared to Lasso, Adaptive Lasso and Boosting are illustrated by Monte Carlo studies and empirical applications to forecasting monthly stock market returns and quarterly output growths.
Keywords: C22; C52; C53; C55; 330; parameter instability; high-dimensionality; variable selection; One Covariate at a time Multiple Testing (OCMT)